1998
DOI: 10.1017/s0305000998003559
|View full text |Cite
|
Sign up to set email alerts
|

Longer-term effects of corrective input: an experimental approach

Abstract: There is growing evidence that corrective input for grammatical errors is widely available to children (Farrar, 1992; Morgan, Bonamo & Travis, 1995). However, controversy still exists concerning the extent to which children can identify and exploit available negative input. In particular, very little is yet known about the longer-term effects of negative input. Performing a time series analysis on observational data, Morgan et al. (1995) conclude that corrective recasts are not related to future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(98 citation statements)
references
References 0 publications
3
93
2
Order By: Relevance
“…The representational improvement, as well as procedural change, found in many children this study is more likely to be indicative of lasting cognitive change (as found in although future studies could employ delayed post-tests to verify this. Saxton et al (1998) has carried out a study into the longer-term effects of this type of corrective modelling and found that improvements in children's linguistic output were sustained five weeks later.…”
Section: Discussionmentioning
confidence: 99%
“…The representational improvement, as well as procedural change, found in many children this study is more likely to be indicative of lasting cognitive change (as found in although future studies could employ delayed post-tests to verify this. Saxton et al (1998) has carried out a study into the longer-term effects of this type of corrective modelling and found that improvements in children's linguistic output were sustained five weeks later.…”
Section: Discussionmentioning
confidence: 99%
“…All eight studies reported positive effects (Baker & Nelson, 1984;Hovell, Schumaker, & Sherman, 1978;McLean & Vincent, 1984;Nelson, 1977;Nelson, Carskaddon, & Bonvillian, 1973;Saxton, 1998;Scherer & Olswang, 1984;.…”
Section: Systematic Reviewmentioning
confidence: 98%
“…She also cites studies showing that corrections from adults can actually improve children's grammars (e.g. Chouinard & Clark, 2003;Demetras et al, 1986;Saxton, 2000;Saxton et al 1998). …”
Section: The Poverty Of the Stimulusmentioning
confidence: 99%